Praktik Konsumsi Makanan Halal Dalam Budaya Lokal (Studi Kasus Antropologi Ekonomi di Komunitas Muslimah Hijaber Palopo) - Muh Nur Kholis; Reza Hilmy Luayyin (Wasīlah: Journal Of Sharia Sciences, 2025)
communities in Palopo, with a specific focus on the Hijaber Palopo community. Halal food consumption is not only perceived as a religious obligation but also as part of social identity and cultural expression. Using an Islamic economic anthropological approach, this research aims to uncover how halal practices are performed, interpreted, and socially constructed within a local context. The study employs a descriptive qualitative method through participant observation, in-depth interviews, and documentation. Findings reveal that halal consumption practices within the Hijaber Palopo community are influenced by local values, the reinforcement of religious identity, and social change driven by the penetration of social media. Halal is not only a religious norm but also a means of community empowerment, social solidarity, and a symbol of Islamic lifestyle and status. This research highlights the importance of understanding local dynamics in the practice of Islamic economics and contributes to the development of a culturally contextual halal discourse.